2015
DOI: 10.1186/s12951-015-0090-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive magnetic near Infra-Red fluorescent core-shell iron oxide/human serum albumin nanoparticles for controlled release of growth factors for augmentation of human mesenchymal stem cell growth and differentiation

Abstract: Background: Iron oxide (IO) nanoparticles (NPs) of sizes less than 50 nm are considered to be non-toxic, biodegradable and superparamagnetic. We have previously described the generation of IO NPs coated with Human Serum Albumin (HSA). HSA coating onto the IO NPs enables conjugation of the IO/HSA NPs to various biomolecules including proteins. Here we describe the preparation and characterization of narrow size distribution core-shell NIR fluorescent IO/HSA magnetic NPs conjugated covalently to Fibroblast Growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 65 publications
3
33
0
Order By: Relevance
“…The iron oxide enables easy detection of the nanoparticles in the target tissue using Prussian blue staining (Levy et al. ). Two hundred and fifty microlitres of IONP solution was injected into rabbit eyes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The iron oxide enables easy detection of the nanoparticles in the target tissue using Prussian blue staining (Levy et al. ). Two hundred and fifty microlitres of IONP solution was injected into rabbit eyes.…”
Section: Resultsmentioning
confidence: 99%
“…; Levy et al. ). Rabbits were anesthetized with an intramuscular injection of ketamine (35 mg/kg) and xylazine (5 mg/kg).…”
Section: Methodsmentioning
confidence: 97%
“…In previous studies, we demonstrated that IONP-delivery of FGF2 can enhance hBMSC growth and differentiation in vitro [34]. In future studies, we will examine the possibility of prolonging graft survival in the EVSC by coinjection with IONPs loaded with growth factors that promote hBMSC survival.…”
Section: Discussionmentioning
confidence: 96%
“…10,164,166 Studies show MSC labeling does not negatively affect cell viability 51 or ability to differentiate, regenerate tissue, and self-renew. 11,104,163 IONPs can also be used to transport SCs and other therapeutic agents. Their transport and location has been monitored in the brain, 26 heart, 68 vasculature, 149 muscle, 3,167 and joints.…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…137 Another strategy is conjugating IONPs with ligands to enhance receptor-mediated endocytosis and increase treatment efficacy. 104 Mechanical and thermal stimulation with different magnetic field regimens would be an interesting area to study as it can affect MSC fate 54,59 and has not been thoroughly explored.…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%